(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Although increased carotid intima-media thickness (cIMT), soluble adhesion molecules and proinflammatory biomarkers are strongly implicated in the development of atherosclerotic lesions, the role of obesity and metabolic syndrome (MetS) in atherogenicity and inflammation among schoolchildren is not well investigated. AIM To determine the levels of cIMT, endothelial dysfunction and inflammatory biomarkers in a group of schoolchildren with obesity and MetS. METHODS Eighty-seven schoolchildren (age 10–15 years) were categorised into three groups: normal bodyweight group, obese group and severely obese with MetS group (17 boys and 12 girls in each group). Levels of cIMT were measured with high-resolution B-mode ultrasound. Serum proinflammatory cytokines interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β), and soluble adhesion molecules E-selectin, vascular cell adhesion molecule-1 (VCAM-1), and intercellular adhesion molecule-1(ICAM-1) were measured. RESULTS Mean cIMT levels were significantly higher (p ≤0.05) among severely obese schoolchildren with MetS (0.49 ± 0.02 mm) compared with both the obese (0.43 ± 0.03 mm) and the normal bodyweight counterparts (0.36 ± 0.03 mm). Serum levels of IL-6, TNF-α, IL-1β, E-selectin, VCAM-1 and ICAM-1 were significantly higher (p ≤0.05) in severely obese with MetS and obese children compared with the normal bodyweight group. However, no significant differences (p >0.05) were found between the severely obese schoolchildren with MetS and the obese without MetS. CONCLUSIONS Severely obese schoolchildren having MetS exhibited higher cIMT levels than obese and normal bodyweight counterparts. Biomarkers of inflammation and endothelial dysfunction were higher in obese schoolchildren, but biomarkers were not increased any further by the degree of obesity nor the MetS cluster.